WOMEN ENTREPRENEURSHIP - A SOLUTION FOR ROMANIAN ECONOMY DEVELOPMENT - Florentina-Georgiana, COJOCARU (Strategii Manageriale)
Entrepreneurship is not only equivalent with a way of increasing national revenue or a source of new jobs, but represents also an important vector of economic growth by forming a bridge between innovation and market. The spectacular evolution and modification of family life as well as professional activity led to the increasing of women in business in the last 25 years, but this growth has brought with it the birth rate decrease. Women have become more important in the global market, not just as an employee, but also as a consumer, entrepreneur, manager and investor. The article aims to capture the difficulties that women entrepreneurship is facing, gender differences and gender diversity in business, but also its impact on the economy. By approaching the theme we intend to highlight the problems faced by women both in terms of concepts, and education by analyzing employment rate by age, status, education level, gender and region, and also an analysis of the statistics on the discouraged people in finding a job by age and sex, and so on. Using the data collected and analyzed we will try to estimate the impact of female entrepreneurship on the Romanian economy.